Peningkatan Kinerja Keuangan Melalui Remunerasi Berbasis Sistem Informasi Akuntansi dan Pengelolaan Keuangan - Yunita Eka Cahyani; Suwandi Suwandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the impact of accounting information systems and financial management on financial performance, with remuneration as a mediating variable. Using a quantitative approach, the research involved 36 respondents from Eyelink Group and its branches. Data were collected through questionnaires and analyzed using Structural Equation Modelling (SEM) with SmartPLS software. The findings indicate that accounting information systems have a positive and significant effect on remuneration, and remuneration positively affects financial performance. However, financial management does not have a direct significant impact on financial performance. Additionally, remuneration mediates the relationship between accounting information systems and financial performance but does not mediate the relationship between financial management and financial performance. These findings provide valuable insights for companies to optimize the use of accounting information systems and remuneration policies to enhance financial performance.